Characterization of Mycobacterium bovis from Humans and Cattle in Namwala District, Zambia. (14th April 2014) - Malama, Sydney; Johansen, Tone Bjordal; Muma, John Bwalya; Munyeme, Musso; Mbulo, Grace; Muwonge, Adrian; Djønne, Berit; Godfroid, Jacques
Abstract : Tuberculosis remains a major public health problem in Zambia. While human to human transmission of Mycobacterium tuberculosis is of major importance in driving the tuberculosis epidemic, the impact of Mycobacterium bovis transmission from infected cattle is largely unknown. This cross-sectional study aimed at molecular characterization of M. bovis in humans and cattle. A total of 100 human sputum samples and 67 bovine tissues were collected and analyzed for the presence of mycobacteria. Of 65 human samples that harbored acid fast bacteria (AFB), 55 isolates were obtained of which 34 were identified as M. tuberculosis and 2 as M. bovis . AFB-positive bovine samples (n = 67 ) yielded 47 mycobacterial isolates among which 25 were identified as M. bovis and no M. tuberculosis was found. Among the M. bovis isolates, spoligotyping revealed a high homogeneity in genotypes circulating in Namwala district. Human and cattle isolates shared identical MIRU-VNTR genotypes, suggesting that transmission between the two hosts may occur. Therefore, this study has documented zoonotic TB in human patients in Namwala district of Zambia. However, further molecular epidemiological studies in the study area are recommended.